The Effect of Contextual Interference and Practice Specificity on Learning a Throwing Skill: A Study of Effortless Process - Fariba Hasan Barani; Behrooz Abdoli; Shaghayegh Modaberi (University of Tehran, 2015)
Recently, researches on motor learning have illustrated that learning with effortless process supports learning under psychological stress. Also, contextual interference and practice specificity theories are among those theories which investigate desired practice conditions. The current study aimed at identifying cognitive effort and effortless process based on contextual interference and practice specificity theories. 30 participants were randomly divided into three groups of specificity, random and serial. After the pretest, groups practiced the throwing task for three days. After two transfer tests, subjects were asked to write down the verbal protocol with all details. The results of combined analysis of variance test (3*3) (group*day) revealed the effect of performance progress in practice days and one-way ANOVA tests revealed a significant difference between specificity and random groups during 1 and 2 transfer tests (P˂0.017). It was concluded that specificity and random groups used effortless and implicit process; therefore, coaches and therapists are recommended to use these two methods to instruct motor skills.